The Impact of Special Allocation Funds (SAF) on The Development Micro Small Enterprises (MSEs) in Indonesia - Wasifah Hanim; Rosnawintang; Sugiartiningsih; Sri Harini (Universitas Djuanda, 2023)
Micro Small Enterprises (MSEs) have an essential role in increasing the capacity of the national economy, contributing to employment, and increasing people's income. However, MSEs need help with significant problems, namely access to finance and capital, technology in the production process, human resource capacity, and marketing. This study aims to explore empirically related to the impact of the flow of Special Allocation Funds (SAF) on the development of micro and small enterprises in Indonesia. The research objectives covered 32 provinces. The data used secondary data collected from 3 (three) sources, consisting of the data on the value of SAF obtained from The Ministry of Finance of the Republic of Indonesia, the data on the number MSEs received from the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia, and the data of GRDP, number of population obtained of Central Bureau of Statistics. This research is a quantitative approach. The Method of analysis used the econometric model, namely the panel regression model, which is a regression that combines time series data (t = 7) and cross-section (i = 32) of the Specification model using the Chow and Hausman test. Based on the fixed effect model (FEM) showed that SAF from the central government to regional governments can significantly develop MSEs in Indonesia. Implies that the programs/activities proposed by the Local Government with SAF funding significantly increase MSEs. Therefore monitoring and evaluation of programs that use SAF funding to improve MSEs must be carried out so that the role of MSEs is getting higher in national/regional development.